A combined treatment system of O3/UV oxidation and activated carbon adsorption: emerging contaminants in hospital wastewater. (15th March 2023) - Nabavi, Erfan; Pourrostami Niavol, Kasra; Dezvareh, Ghorban Ali; Khodadadi Darban, Ahmad
Abstract: Researchers have recently focused their attention on emerging contaminants (ECs) in wastewater because they pose serious health and environmental risks. Because ECs are persistent in the environment and have the ability to disrupt the physiology of target receptors, they have been labeled as contaminants of recent environmental concern. For removing various ECs, a variety of treatment technologies have been developed, including biological, chemical, and physical methods. However, no single technology can currently effectively remove ECs, whereas hybrid systems have consistently proven to be more effective. Furthermore, the majority of existing technologies are energy and resource intensive, as well as expensive to maintain and operate. Furthermore, the majority of advanced treatment technologies that have been proposed have yet to be evaluated for large-scale feasibility. Some ECs, particularly pharmaceuticals and pesticides, were found to be significantly removed using a hybrid technique that included ozone/UV and granular activated carbon (GAC). Besides, the removal of effluent parameters (TDS, COD, TOC) was enhanced through the GAC surface oxidization as a catalyst with NaOH before the process and by ozone within the procedure as well. HIGHLIGHTS: Combined oxidation and adsorption treatment strategy in hospital wastewater. A photocatalytic ozonation system was designed to remove amoxicillin. A CGCT + UV system showed great performance in the removal of amoxicillin. An optimization model was developed statistically using RSM. Graphical Abstract